Mixed Strategy Dalam Persaingan Bisnis Industri Pengolahan Kopi Bubuk - Giovanni, Arrenda; Nadapdap, Hendrik Johannes (Universitas Pendidikan Ganesha, 2021)
This study provides the formulation of Mixed Strategy on a business Kopi Babah Kacamata doing processing coffee beans to coffee powder. This study aims to knows and analyzing quadrant position Kopi Babah Kacamata, formulation of Mixed Strategy, and impact on the application of the formulation of Mixed Strategy in competition business manufacture industry coffee beans at Salatiga city. This type of research was a qualitative study and the technique of determining participants used a purposive sample. The analytical method used method SWOT analysis and Mixed Strategy analysis (Blue Ocean Strategy dand White Ocean Strategy) and for test data validity using the triangular method. Based on the SWOT analysis Kopi Babah Kacamata is in the 1st (progestin) according to SO strategy that increases the productivity and quality of coffee, and make used coffee trend to access the market wider in business competition. Mixed Strategy analysis of Kopi Babah Kacamata is taking a new strategy in a way that reduces factors unimportant in business and Increase could factor winning competition, then created Something never offered. Kopi Babah Kacamata indirectly can maintain business with a positive impact on the general public and the environment. The impact of the application a Mixed Strategy to the company can be winning a competitive way created a new market and exist the company.